1999
DOI: 10.1074/jbc.274.8.4924
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Phospholipid Hydroperoxide Glutathione Peroxidase Plays a Major Role in Preventing Oxidative Injury to Cells

Abstract: Phospholipid hydroperoxide glutathione peroxidase (PHGPx) is synthesized as a long form (L-form; 23 kDa) and a short form (S-form; 20 kDa). The L-form contains a leader sequence that is required for transport to mitochondria, whereas the S-form lacks the leader sequence. A construct encoding the leader sequence of PHGPx tagged with green fluorescent protein was used to transfect RBL-2H3 cells, and the fusion protein was transported to mitochondria. The L-form of PHGPx was identified as the mitochondrial form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
168
1
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 261 publications
(182 citation statements)
references
References 46 publications
8
168
1
5
Order By: Relevance
“…CHEN et al [220] have recently demonstrated that depletion of mitochondrial GSH in human umbilical vein endothelial cells (HUVECs) increased TNF-a-induced adhesion molecule (VCAM-1) expression but not ICAM-1 expression and mononuclear leukocyte adhesion in HUVECs, suggesting that mitochondrial GSH is involved in endothelial cell function [220]. Recent studies have shown that gene delivery of glutathione reductase to mitochondria and overexpression of GPx in various cell lines provided protection against oxidative stress [224,225]. This finding demonstrates the importance of mitochondrial GSH homeostasis in the regulation of cell function.…”
Section: Oxidant-mediated Mitochondrial Damagementioning
confidence: 99%
“…CHEN et al [220] have recently demonstrated that depletion of mitochondrial GSH in human umbilical vein endothelial cells (HUVECs) increased TNF-a-induced adhesion molecule (VCAM-1) expression but not ICAM-1 expression and mononuclear leukocyte adhesion in HUVECs, suggesting that mitochondrial GSH is involved in endothelial cell function [220]. Recent studies have shown that gene delivery of glutathione reductase to mitochondria and overexpression of GPx in various cell lines provided protection against oxidative stress [224,225]. This finding demonstrates the importance of mitochondrial GSH homeostasis in the regulation of cell function.…”
Section: Oxidant-mediated Mitochondrial Damagementioning
confidence: 99%
“…The most abundant GPx4 of testis is associated with mitochondria (16). Overexpression of mitochondrial GPx4 in RBL2h3 cells suppresses mitochondrial-derived reactive oxygen species produced by the respiratory chain inhibitors (17) and suppresses apoptosis induced by 2-deoxyglucose, staurosporine, etoposide, and UV (18,19). In spermatozoa, GPx4 is also mainly localized in the mitochondria (13,16).…”
mentioning
confidence: 99%
“…Next we studied the expression of H 2 O 2 metabolizing en- (25). RT-PCR analysis showed that the expression of 2 types of GPx (cGPx and PHGPx) that are expressed in mitochondria (25) was increased in SK-Hep1 0 cells compared with parental cells (Fig.…”
Section: Increased Ros Production During 0 Cell Derivation But Not Inmentioning
confidence: 99%